Osificación heterotópica del mesenterio. Reporte de un caso - José Alejandro Díaz Castillo; Francisco Solano Perdomo; Juan Pablo Ruíz Pineda; Vélez Cuorvo Luisa Fernando; Fabio Andrés Morales Espinoza (Case Reports)
Resumen